1999
DOI: 10.1046/j.1365-3156.1999.00397.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic of self‐poisoning with seeds of the yellow oleander tree (Thevetia peruviana) in northern Sri Lanka

Abstract: Deliberate self-harm is an important problem in the developing world. Ingestion of yellow oleander seeds (Thevetia peruviana) has recently become a popular method of self-harm in northern Sri Lanka -- there are now thousands of cases each year. These seeds contain cardiac glycosides that cause vomiting, dizziness, and cardiac dysrhythmias such as conduction block affecting the sinus and AV nodes. This paper reports a study of the condition's mortality and morbidity conducted in 1995 in Anuradhapura General Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
101
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(105 citation statements)
references
References 18 publications
2
101
0
2
Order By: Relevance
“…Studies on the insecticidal activity of Jatropha curcas have been reported by HABOU et al (2011). The use of Thevetia peruviana fruits for suicide attempts has been reported in Sri Lanka and southern India (EDDLESTON et al 1999). KHANAM et al (2008) tested Sapium indicum WILLD., Thevetia neriifolia JUSS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the insecticidal activity of Jatropha curcas have been reported by HABOU et al (2011). The use of Thevetia peruviana fruits for suicide attempts has been reported in Sri Lanka and southern India (EDDLESTON et al 1999). KHANAM et al (2008) tested Sapium indicum WILLD., Thevetia neriifolia JUSS.…”
Section: Discussionmentioning
confidence: 99%
“…Eddleston et al in their observation reported that out of 1939 cases admitted males were 1021 (52.7%). 6 In this study, 76% patients consumed crushed seeds, 22% patients consumed whole seeds, 2% patients consumed leaves and none consumed fruit. So crushed seeds consumption were more common in our study.…”
Section: Discussionmentioning
confidence: 57%
“…Patients usually presents with hyperkalemia. 6 In this study authors tried to find the presence of various arrhythmias and its association with duration and form of exposure of yellow oleander. Since hyperkalemia is a usual manifestation in yellow oleander poisoning, authors attempted to find association between serum potassium, calcium and magnesium levels and the arrhythmias in yellow oleander poisoning in this study.…”
mentioning
confidence: 99%
“…From the 1960s, increases in the suicide rate were driven by pesticides poisoning and, since the 1980s, by kanēru (yellow oleander) seed poisoning (De Silva et al 2012;Eddleston, Sheriff, & Hawton 1998;Eddleston et al 1999;Eddleston & Phillips 2004). Correspondingly, decreases in the suicide rate were achieved following restrictions placed on the import and sale of WHO Class 1 toxicity pesticides in 1995 and endosulfans in 1998, as well as improved medical treatment for pesticide and kanēru poisoning (Gunnell et al 2007;Roberts et al 2003).…”
Section: Suicide Methods At National Levelmentioning
confidence: 99%